The Development of a Community-Based Model as an Assisting Approach in the Prevention of Pregnancy and Labor Complications in Pandeglang Regency, Banten, Indonesia - Yudhia Fratidhina; Nina Herlina; Hamidahs; Sri Mulyati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Most of the direct causes of maternal death is obstetrical complications. Some programs have been doneto reduce the incidence of complications on pregnancy and childbirth complications unfortunately theimplementation of the program has not been maximized. Community empowerment is required to ensurethe sustainability of the program. This research was conducted to develop community-based Model inpreventing pregnancy and labor complications based on asset and community participatory. This researchwas conducted with a mixed method approach. On the stage of model development is conducted qualitativelythrough Focus Group Discussion and in-depth interview with 4 key informants and 13 support informants.Furthermore, model is developed quantitatively by using cross sectional study design on 80 respondents.The analysis that used in this research is SEM PLS. Once the model is formed, the evaluation was conductedon 83 respondents by using pre and post-test design. Application of community-based Model in the societyis done by mentoring models using Module of asset and participatory-based prevention of pregnancy andlabor complication through community-based Model. The results show that community-based modelcan be achieved through community participation, community assets development, knowledge, attitudesand behavior. The results also reveal that the community-based model is statistically proven to increaseknowledge (p 0.000), attitude (p 0.000) and the behavior of expectant mother (p. 0.000). Community-basedModel consists of five variables and it was proved to be effective in improving the knowledge, attitude andbehavior of expecting mothers on the prevention of pregnancy complication and childbirth.